2020
DOI: 10.1053/j.ajkd.2020.02.451
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Immune Checkpoint Inhibitors in Patients on Dialysis: A Retrospective Case Series

Abstract: important intellectual content during manuscript drafting or revision and agrees to be personally accountable for the individual's own contributions and to ensure that questions pertaining to the accuracy or integrity of any portion of the work, even one in which the author was not directly involved, are appropriately investigated and resolved, including with documentation in the literature if appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 10 publications
1
15
0
1
Order By: Relevance
“…With respect to severe (i.e. Grade 4) irAEs, notable reported events included one death in the context of encephalitis, one (nonfatal) episode of myocarditis and two (nonfatal) pneumonitis events [ 5 ]. The death associated with encephalitis was the only reported fatal event attributed to therapy.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to severe (i.e. Grade 4) irAEs, notable reported events included one death in the context of encephalitis, one (nonfatal) episode of myocarditis and two (nonfatal) pneumonitis events [ 5 ]. The death associated with encephalitis was the only reported fatal event attributed to therapy.…”
Section: Introductionmentioning
confidence: 99%
“… 6 In addition, a report of 19 dialysis patients who received ICI therapy between 2013 and 2019 showed that although 32% of the patients experienced diverse immune-related adverse effects, none of the 4 patients with previous failed kidney allografts included in the study had clinical evidence of rejection. 7 …”
Section: Discussionmentioning
confidence: 99%
“…5 A T cell–mediated rejection is an almost universal finding whenever a biopsy specimen is obtained, with approximately 50% of cases representing mixed acute T cell–mediated and antibody-mediated rejection whereas pure T cell–mediated rejection is diagnosed in the other 50%. 6 , 7 Of note, a considerable percentage of cases remained unspecified in most studies. 4 Our patient’s biopsy specimen revealed lesions highly suggestive of mixed acute rejection in accordance with the aforementioned pathologic patterns described in patients with functioning kidney grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strohbehn et al presented a brief report of treatment response and side effects in 19 ESRD patients received ICI therapy. However, the study population were quite heterogeneous in cancer types (six genitourinary cancer, three melanoma, three merkel cell carcinoma, three head and neck cancer), ICI regimen (90% anti-PD-1/PD-L1, 5% anti-CTLA-4 and 5% combined anti-PD-1/CTLA-4), and dialysis modality (79% hemodialysis, 21% peritoneal dialysis), which limited to achieve a definite conclusion (32). Compared with previous reports, our study revealed more hematologic AEs, 36.4% of which were grade 3-4 neutropenia.…”
Section: Discussionmentioning
confidence: 99%